2016
DOI: 10.1245/s10434-016-5418-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Infusion in Combination with Modern Systemic Chemotherapy is Associated with Improved Survival Compared with Modern Systemic Chemotherapy Alone in Patients with Isolated Unresectable Colorectal Liver Metastases: A Case–Control Study

Abstract: In this case-control study of patients with IU-CRCLM, HAI in combination with CT was associated with improved OS when compared with modern systemic CT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…More than half of patients diagnosed with colorectal cancer present with or eventually develop liver metastases, only 10%-20% of which are resectable at presentation. A percentage of these metastases may be downstaged for surgery by treatment with chemotherapy and targeted agents (2,3). However, patients with liver metastases which remain unresectable have a poor prognosis and are generally given second-line chemotherapy, with a median survival of approximately one year (3).…”
Section: Introductionmentioning
confidence: 99%
“…More than half of patients diagnosed with colorectal cancer present with or eventually develop liver metastases, only 10%-20% of which are resectable at presentation. A percentage of these metastases may be downstaged for surgery by treatment with chemotherapy and targeted agents (2,3). However, patients with liver metastases which remain unresectable have a poor prognosis and are generally given second-line chemotherapy, with a median survival of approximately one year (3).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, HAIP use is indicated for patients with unresectable CRLM or as adjuvant therapy after operation among patients at high risk of hepatic recurrence . When used in combination with modern systemic chemotherapy for unresectable CRLM, HAIP therapy is associated with response rates of 55% to 88%, median overall survival of nearly 3 years, and half of the patients convert to resectable . In addition, conversion to potentially resectable disease occurs in nearly half of the patients …”
Section: Introductionmentioning
confidence: 99%
“…Despite encouraging results, utilization of HAIP for CRLM remains limited to a few centers . Establishing a HAIP program is labor intensive and requires the expertize of medical oncologists, chemotherapy pharmacists, nurses, surgeons, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Pak et al report the findings from a prospective phase II trial evaluating combination HAI and systemic chemotherapy, wherein 47 of the 64 enrolled patients with unresectable hepatic metastases (73%) responded to treatment, and 33 were converted to resectable disease (52%). Similarly, a case‐control study from Pittsburgh found that patients who underwent treatment with HAI plus systemic chemotherapy had a median overall survival of 32.8 months compared with 15.3 months in the chemotherapy alone group ( P < 0.001) …”
Section: Liver‐directed Therapiesmentioning
confidence: 82%